Poliovirus shedding after the first and second doses of trivalent polio vaccines in newborns - Viramitha K. Rusmil; Meita Dhamayanti; Sunarjati Soedigdo Adi; Imam Megantara (Indonesian Pediatric Society, 2015)
Background The trivalent oral polio vaccine (tOPV) produced by Bio Farma consists of three live, attenuated poliovirus serotypes (1, 2, and 3). The tOPV stimulates the formation of secretory IgA (sIgA) on the intestinal wall and lumen. The existence of sIgA is considered giving immunity in the intestines, it could prevent the spread of viral replication and thus inhibit the transmission of the polio virus.Objective To determine the differences in shedding after each of the first two tOPV immunizations in newborns.Methods This one-way repeated measure study was conducted in newborns from three primary health centers in Bandung, West Java. After administering tOPV to newborns, we assessed the shedding of poliovirus in their stool specimens at 30 days after the first dose and 7 days after the second dose. Data was analyzed using McNemar test with 95% confidence intervals (CI) to differentiate the shedding of poliovirus after the first and second doses.Results Of 150 children, 128 subjects completed the study. At 30 days after the first tOPV dose, 26 subjects (20.3%) were negative for shedding of poliovirus in stool specimens. Of the 102 subjects who had poliovirus isolated from their stools, the serotypes comprised of polio 1: 10.9%, polio 2: 14.8%, polio 3: 45.3%, polio 1 and 3: 3.1%, polio 2 and 3: 4.7%, and polio 1,2, and 3: 0.8%. At 7 days after the second tOPV dose, there was a significant increase in subjects negative for shedding of poliovirus (78 subjects; 60.9%). Statistical analysis revealed significantly decreased shedding of poliovirus in stool specimens between the first and second doses of tOPV (P<0.05 ).Conclusion There is a significantly decreased number of subjects with shedding of poliovirus in stool specimens 7 days after the second tOPV dose than at 30 days after the first tOPV dose.